CNS activity of the methanol extracts of Careya arborea in experimental animal model - Ramanathan Sambath Kumar; R Shanmuga Sundram; P. Sivakumar; R. Nethaji; V. Senthil; N. Venkateswara Murthy; R. Kanagasabi (Bangladesh Pharmacological Society, 2008)
The aim of the present study is to investigate central nervous system (CNS) activity of the methanol extract of barks of Careya arborea (Myrtaceae) in Swiss albino mice and Wistar albino rats. General behavior, exploratory behavior, muscle relaxant activity and phenobarbitone sodiuminduced sleeping time were studied. The results revealed that the methanol extract of barks of Careya arborea at 100 and 200 mg/kg caused a significant reduction in the spontaneous activity (general behavioral profile), remarkable decrease in exploratory behavioral pattern (Ymaze and head dip test), a reduction in muscle relaxant activity (rotarod and traction tests), and also significantly potentiated phenobarbitone sodiuminduced sleeping time. The results suggest that methanol extract of Careya arboreaexhibit CNS depressant activity in tested animal models.